Development of Local Potential-Based Animal Website Learning Media for Senior High School Students - Juniarti, Astri; Hidayat, Saifullah; Adi, Widi Cahya (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
Contextual learning, which integrates learning materials with the students' real environment, can make learning more meaningful for the students. This research aims to assess the feasibility of the Animal Website development product as a learning media. The research adopts the Research and Development (R&D) methodology with the 4D development model (Define, Design, Develop, and Disseminate). However, the developed product only reached the Develop stage. The study was conducted at Senior High School with students from the 11th and 12th grade of the Science Program (MIPA) as the research subjects. Data collection techniques involved interviews and questionnaires, while data analysis employed qualitative and quantitative analysis methods. The validation results the Animal Website learning media, which incorporates animal-related materials based on the local potential of Bangka Island, is of very good quality and highly suitable for use in the learning process.ABSTRAK: Konsep pembelajaran kontekstual yang mengintegrasikan materi pembelajaran dengan lingkungan nyata peserta didik dapat menjadikan pembelajaran peserta didik jadi lebih bermakna. Penelitian ini bertujuan untuk menguji kelayakan produk pengembangan Animal Website sebagai media pembelajaran. Penelitian ini menggunakan metode penelitian Research and Development (R&D) dengan model pengembangan 4D (Define, Design, Develop, and Disseminate. Akan tetapi, produk yang dikembangkan hanya sampai pada tahap Develop. Penelitian dilakukan di MAN (Madrasah aliyah Negeri) dengan subjek penelitian peserta didik kelas XI dan XII MIPA. Teknik pengambilan data berdasarkan wawancara dan angket. Sedangkan, teknik analisis data menggunakan teknik analisis data kualitatif dan kuantitatif. Hasil validasi Animal Website materi animalia berbasis potensi lokal Pulau Bangka memiliki kualitas sangat layak untuk digunakan dalam proses pembelajaran.